Utilization of Scenedesmus obliquus Protein as a Replacement of the Commercially Available Fish Meal Under an Algal Refinery Approach - Patnaik, Reeza; Singh, Naveen Kumar; Bagchi, Sourav Kumar; Rao, Pavuluri Srinivasa; Mallick, Nirupama (Frontiers in Microbiology, 2019)
The approach of algal refinery as a method to reduce the cost of algal biodiesel by co-production of various value-added chemicals is the most up-coming strategy suggested for the economic viability of microalgal biodiesel. This concept being relatively new and novel, abundant literature on the subject is not available although fragmented data on some feedstocks are present. The main objective of this research paper is to propose an algal refinery design through utilization of Scenedesmus obliquus biomass for production of various industrially-important products. For this purpose, first a protocol was standardized for maximum extraction of protein from S. obliquus biomass. Then, different experiments were conducted for 90 days each to find out the optimum concentration of microalgal protein that can be substituted in the diets of freshwater fishes for their maximum growth. During these experiments eight different growth parameters and seven water quality parameters were tested. Results showed that the standard + whole microalgal biomass + extracted microalgal protein diet (25:25:50) was the best diet for maximum growth of the freshwater fishes. After conducting these experiments, a detailed sequential extraction process for maximum valorisation of the S. obliquus biomass or in other words an algal refinery was designed. The detailed sequential process developed, yielded 0.06 g of β-carotene, 10 g of protein, 38 g (43 mL) of biodiesel, 2 g of omega-3 fatty acid, 3 g (2.4 mL) of glycerol and 18 g (23 mL) of bioethanol from 1 Kg wet (≈100 g dry) S. obliquus biomass thus converting 70% of the test microalgal biomass into biodiesel and other value-added products by using an algal refinery approach.